Rural growth linkages, poverty, and income distribution - Balisacan, Arsenio M. (1992)
The paper provides a survey of selected topics and issues in the economics of rural development, namely: concepts and empirical regularities concerning rural growth linkages, poverty, and income distribution; determinants of income source diversification; and demand and supply factors constraining rural growth linkages in the Philippines. The survey draws implications for public policy and further research on the economics of agriculture and rural development.
Includes bibliographical references (pages 80-85).
Keywords: Rural conditions; Philippines -- Economic conditions